Zarządzanie portfelem klientów - Michalska-Dudek, Izabela (Clients Portfolio Management, 2005)
The article presents the essence of customer relationship management and its tasks in assisting of consumer life cycle. In the content there is also a description of creating customer relationship stages, methods of generating clients portfolio and its management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 226-238